Delusion in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2012)
Surviving witnesses talk about seeing things like monsters and swarms of bees. They describe sudden, overwhelming feelings of fear and rage and paranoia. When forensics gives its report, the mass delusions make more sense: It appears the bar patrons were exposed to a cocktail of chemicals and illegal drugs that could drive anyone to temporary insanity, if not kill them outright. And if Eve can't figure it out fast, it could happen again, anytime, anywhere.